The role of cytochrome P450 genetic variants in pesticide metabolism and the risk of child neurodevelopment: a systematic review - Chilipweli, Peter M.; Kidenya, Benson R.; Nyanza, Elias C.; Ngowi, Aiwerasia Vera; Manji, Karim (Frontiers in Pediatrics, 2025)
IntroductionChild neurodevelopment is influenced by genetic variants in cytochrome P450 (CYP450) enzymes, which affect detoxification and oxidative stress pathways. These variations modulate susceptibility to environmental toxins, influencing brain development through gene–environment interactions that impact neurogenesis, synaptogenesis, and inflammation, potentially contributing to neurodevelopmental disorders. This review has a major question to answer: how do CYP450 gene polymorphisms modulate pesticide metabolism and contribute to neurodevelopmental risks in children?MethodThis study has been conducted according to PRISMA and includes studies conducted from 2005 to 2025. It has been registered to PROSPERO with the number PROSPERO 2024 CRD42024617478. The databases used for the search included PubMed/MEDLINE, Embase, Scopus, and African Journals Online (AJOL). Additional sources, such as OpenGrey, institutional repositories, and conference proceedings, were also searched using targeted search strategies and robust inclusion criteria, which were employed in study selection and final review to analyze gene–environment interactions and developmental outcomes.ResultsA total of 758 studies were identified through database searches and manual reference checks. After eliminating studies due to various factors, 176 eligible studies were selected by reviewing the titles and abstracts. Finally, a total of nine articles were included in this systematic review. The review identified CYP3A4 as the most polymorphic gene, followed by CYP2C9, CYP2B6, and CYP1A2—all involved in pesticide metabolism, particularly organophosphates such as chlorpyrifos. Evidence from nine studies suggests that CYP450 polymorphisms influence pesticide detoxification capacity, increasing neurodevelopmental risks in exposed children. These findings highlight the importance of genetic risk assessment in public health strategies targeting pesticide-exposed populations.ConclusionThis review highlights the role of CYP450 gene polymorphisms in increasing susceptibility to pesticide-related neurotoxicity, especially in children and agricultural workers, emphasizing the need for genetically based risk assessment in public health strategies.Systematic Review RegistrationPROSPERO CRD42024617478.